Political Strategy of Nahdlatul Ulama Party in Cirebon Regency during 1952-1967 - Ahmad Faiz Rofi'i; Yety Rochwulaningsih; Alamsyah Alamsyah (Diponegoro University, 2022)
At the 1952 Nahdlatul Ulama (NU) Congress in Palembang, 1952, NU officially broke away from Masyumi and declared itself a political party. From then on, NU emerged as a growing force in both local and national political scenes. In the 1955 elections in Cirebon, the NU party emerged as the winner and the only branch in West Java that received the most votes. The political strategy of the NU Party in Cirebonin the run-up to the 1955 general election was based on the instructions of the Nahdlatul Ulama Executive Board (PBNU) to immediately organize party activities; among others by recruiting non-party members and preparing funding. The emergence of local kiai (religious leaders) who had extensive networks in the villages and Islamic boarding schools also contributed to the NU party’s victory. After the 1955 elections, the Cirebon NU Party highlighted unilateral actions by the PKI. During the September 30, 1965 Movement (Gestapu), mass killings broke out in Central Java and East Java but similar violence did not occur in Cirebon, though there was small outbreaks of violence. In response to the political situation in Indonesia and considering the situation at the local level, PBNU held its 24th Congress in Bandung 1967. By employing the historical method, this study discusses the political strategy of the NU party in Cirebon Regency before and after the 1955 election.